2009
DOI: 10.1007/s00249-008-0401-1
|View full text |Cite
|
Sign up to set email alerts
|

Dense chromatin plates in metaphase chromosomes

Abstract: In a previous work we observed multilayered plate-like structures surrounding partially denatured HeLa chromosomes at metaphase ionic conditions. This unexpected finding has led us to carry out an extensive investigation of these structures. Our results show that plates can also be found in metaphase chromosomes from chicken lymphocytes. We have used atomic force microscopy (AFM) to image and investigate the mechanical properties of plates in aqueous solution. Plates are thin (approximately 6.5 nm each layer) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(106 citation statements)
references
References 92 publications
13
93
0
Order By: Relevance
“…In these studies, it has to be taken into account that a significant part of the chromosome volume is occupied by water [67]. This and the relatively weak association between chromatin layers [15,16] suggest that chromosome structure may be dynamic. The rapid diffusion observed for topoisomerase II and other proteins in mitotic chromosomes in vivo [68][69][70] is consistent with the possibility that condensed chromatids are actually very dynamic structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In these studies, it has to be taken into account that a significant part of the chromosome volume is occupied by water [67]. This and the relatively weak association between chromatin layers [15,16] suggest that chromosome structure may be dynamic. The rapid diffusion observed for topoisomerase II and other proteins in mitotic chromosomes in vivo [68][69][70] is consistent with the possibility that condensed chromatids are actually very dynamic structures.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is very likely that the energy 1 nn that stabilizes the stacking of the successive layers in chromosomes is essentially due to face-to-face interactions between nucleosomes. The energy per nucleosome in internucleosome interactions has been obtained experimentally [21,22] and in modelling studies [25 -27] in several laboratories (see Introduction); taking into account all the values obtained in these studies, it is reasonable to consider that 1 nn % 3.4 -14 k B T. On the other hand, the easy sliding between layers in chromatin plates observed in electron microscopy experiments [15,16], suggested that the forces holding the chromatin filament within a layer are higher that the interactions between adjacent layers. This is consistent with the relatively large the Young modulus [15] and the high mechanical resistance [17] found for chromatin plates in AFM experiments in aqueous media, and indicates that the energy 1 wl stabilizing the structure of layers is higher than 1 nn .…”
Section: Surface Energy Differences Of Stacked Chromatin Layers Can Ementioning
confidence: 99%
See 2 more Smart Citations
“…6E-G (Caravaca et al, 2005;Gállego et al, 2009), metaphase chromosomes are very compact, even using buffers containing relatively low concentrations of Mg 2+ (5 mM) or polyamines (0.35 mM). Similar results were obtained in scanning electron microscopy experiments with chromosomes prepared in buffers containing 5 mM Mg 2+ (Adolph and Kreisman, 1983) or different concentrations of polyamines [0.7 mM (Sone et al, 2002); 0.35 mM (Gállego et al, 2009)]. Condensed metaphase chromosomes are compact but at the same time they are extremely soft structures that become easily distorted during the preparation process.…”
Section: Condensed Chromosomesmentioning
confidence: 99%